Oral nutrition supplement improves nutrition and inflammation of cancer patients by regulating iron metabolism - Xuelong Li; Changxing Cui; Wenjing Gong; Guangrun Li; Fubo Song; Peng Huang (International Journal of Food Properties, 2023)
The relationship between cancer and iron metabolism has received more attention, but there is less research on nutritional support to improve the nutritional and inflammatory status of cancer patients by regulating iron metabolism. A survey was conducted involving 90 patients with lung cancer. The control group was given routine hospitalization diet and the oral nutrition supplement (ONS) group was given oral nutrient solution on the basis of routine hospitalization diet. It lasted for 2 weeks. The changes of iron metabolism, nutritional status, and inflammatory indicators of the two groups were compared. After 2 weeks of intervention, the levels of ALB and PA in the ONS group were increased than that in the control group (P < .05), the inflammation was significantly decreased in the ONS group (P < .05), and the levels of Hb, SI, and TIBC in the ONS group were higher than that in the control group, while the SF was significantly reduced (P < .05). ONS could improve iron metabolism, nutritional status, and inflammatory levels. We speculate that the decrease in inflammation may be due to the changes of iron metabolism, thereby improving nutritional status. It may become a new target for tumor treatment.